2020
DOI: 10.1007/s00232-020-00153-y
|View full text |Cite
|
Sign up to set email alerts
|

Partial Reactions of the Na,K-ATPase: Determination of Activation Energies and an Approach to Mechanism

Abstract: Kinetic experiments were performed with preparations of kidney Na,K-ATPase in isolated membrane fragments or reconstituted in vesicles to obtain information of the activation energies under turnover conditions and for selected partial reactions of the Post-Albers pump cycle. The ion transport activities were detected with potential or conformation sensitive fluorescent dyes in steady-state or time-resolved experiments. The activation energies were derived from Arrhenius plots of measurements in the temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…For example, it has been suggested that the E 1 -P(Na 3 ) → E 2 -P transition, associated with the release of Na + to the extracellular environment, could become rate limiting at cold temperatures because its rate decreases steeply below 15 °C in the shark rectal gland Na + /K + -ATPase ( 37 ). In a more recent, detailed study, it has been shown that as temperature becomes colder, the opening of the extracellular gate that allows Na + to be released becomes the rate-limiting step in the transport cycle ( 38 ). Indeed, the occlusion/deocclusion transition that exposes the first Na + to the extracellular environment carries large entropic and enthalpic changes ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been suggested that the E 1 -P(Na 3 ) → E 2 -P transition, associated with the release of Na + to the extracellular environment, could become rate limiting at cold temperatures because its rate decreases steeply below 15 °C in the shark rectal gland Na + /K + -ATPase ( 37 ). In a more recent, detailed study, it has been shown that as temperature becomes colder, the opening of the extracellular gate that allows Na + to be released becomes the rate-limiting step in the transport cycle ( 38 ). Indeed, the occlusion/deocclusion transition that exposes the first Na + to the extracellular environment carries large entropic and enthalpic changes ( 39 ).…”
Section: Discussionmentioning
confidence: 99%